2014
DOI: 10.1080/15332691.2013.871615
|View full text |Cite
|
Sign up to set email alerts
|

Examining Parental Alliance for Low-Income Participants Who Attended Relationship Education With or Without a Partner

Abstract: Couples and relationship education (CRE) programs indicate pos-itive results for low-income couples who attend. However, most studies examined relationship satisfaction or communication patterns, with few addressing the influence of CRE on parental alliance and even fewer examining parental alliances for those who attend couples-level and individual-level programs. Thus, we examined changes in parental alliance for participants who attended CRE individually (n = 182) and with their partner (n = 190). Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…However, in a meta-analysis of relationship education programs-heavily weighted toward two large-scale national dissemination effortslow-income couples failed to show a significant between-groups effect on couples' coparenting (Cohen's d ϭ 0.03; Hawkins & Erickson, 2015). In contrast, uncontrolled designs consistently show significant within-group improvements in low-income couples' coparenting/parental alliance (Adler-Baeder et al, 2013;Carlson et al, 2014). For example, the same meta-analysis previously described found a significant, small-sized intervention effect on coparenting (within-group d ϭ 0.251; Hawkins & Erickson, 2015).…”
Section: Relationship Interventions Improve the Coparenting Relationshipmentioning
confidence: 99%
“…However, in a meta-analysis of relationship education programs-heavily weighted toward two large-scale national dissemination effortslow-income couples failed to show a significant between-groups effect on couples' coparenting (Cohen's d ϭ 0.03; Hawkins & Erickson, 2015). In contrast, uncontrolled designs consistently show significant within-group improvements in low-income couples' coparenting/parental alliance (Adler-Baeder et al, 2013;Carlson et al, 2014). For example, the same meta-analysis previously described found a significant, small-sized intervention effect on coparenting (within-group d ϭ 0.251; Hawkins & Erickson, 2015).…”
Section: Relationship Interventions Improve the Coparenting Relationshipmentioning
confidence: 99%
“…Understanding the individual and relational benefits when one member of a couple attends without his or her partner may be necessary to sustain RE programming for low-income populations over time. A handful of studies examined relational outcomes when only one member of a couple attended RE (Antle et al, 2013;Carlson, Barden, et al, 2014;Visvanathan, Richmond, Winder, & Koenck, 2015;Wadsworth et al, 2011). Results indicated some benefits when one member of a couple attended (Wadsworth et al, 2011).…”
Section: Attending Re Individuallymentioning
confidence: 99%
“…The benefits of RE for couples and individuals who participate with elevated levels of relational and/or individual distress have not been clearly established (Markman & Rhoades, 2012). Additionally, early RE research focused on couples who attended together, whereas recent studies have examined the benefits for participants who attended RE without their partner (Antle, Karam, Christensen, Barbee, & Bibhuti, 2011;Carlson, Barden, Daire, & Swartz, 2014). The study presented here is in response to the call for more research examining baseline participant distress as a moderating factor of RE outcomes (Fawcett, Hawkins, Blanchard, & Carroll, 2010;Markman & Rhoades, 2012), for participants attending as a couple or individually.…”
Section: Introductionmentioning
confidence: 99%
“…The CRE field has a modest record of examining pedagogical and programmatic processes that facilitate positive change in outcomes (Allgood & Higginbotham, ; Bradford, Adler‐Baeder, Ketring, & Smith, ; Carlson, Barden, Daire, & Swartz, ; Higginbotham & Myler, ; Owen, Antle, & Barbee, ; Owen, Rhoades, Stanley, & Markman, ; Quirk, Owen, Inch, France, & Bergen, ). Also, several studies have found that program effects are moderated by baseline levels of individual and dyadic risk and distress, with greater risk and distress generally predicting greater improvement in intervention outcomes (Allen, Rhoades, Stanley, Loew, & Markman, ; Amato, ; Barton, Futris, & Bradley, ; Bodenmann, Hilpert, Nussbeck, & Bradbury, ; Carlson, Rappleyea, Daire, Harris, & Liu, ; DuPree, Whiting, & Harris, ; Epstein et al, ; Halford et al, ; Halford, Sanders, & Behrens, ; Hawkins & Erickson, ; McGill et al, ; Quirk, Strokoff, Owen, France, & Bergen, ; Schilling, Baucom, Burnett, Allen, & Ragland, ; Williamson et al, ).…”
mentioning
confidence: 99%